Answer:
Step-by-step explanation:
We can solve the height of a square pyramid using the Pythagoras theorem, this is because the slant height the height and the section of the base form a right triangle
the slant height is equivalent to the hypotenuse
the height is equivalent to the opposite
while the base(half) is the adjacent
Given
the base of the pyramid= [tex]22.2 in[/tex]
the adjacent is = [tex]\frac{22.2}{2} = 11.1 in[/tex]
the slant height (hypotenuse)= [tex]88.2 in[/tex]
we know that Pythagoras theorem states that "The sum of the squares of the lengths of the legs of a right triangle ('a' and 'b' in the triangle) is equal to the square of the length of the hypotenuse ('c').
[tex]c^2=a^2 + b^2[/tex]
[tex]hyp^2=opp^2+adj^2[/tex]
substituting we have
[tex]88.2^2=opp^2+11.1^2\\opp^2= 88.2^2-11.1^2\\opp^2=7779.24-123.21\\opp^2=7656.03\\opp=\sqrt{7656.03} \\opp=87.498\\opp=87.50 in[/tex]